Use of a polyethylene glycol solution for the management of sand impaction in three dogs. Issue 3 (19th June 2021) - Johnson, Randi; Wigglesworth, Samantha; Moyle, Rachel; Lynch, Alex
Abstract: Three dogs were hospitalized for management of acute gastrointestinal signs secondary to sand impaction. Hospitalized care with administration of a polyethylene glycol (PEG) solution via nasogastric tube. Variable PEG solution doses were used in these dogs (range 72–109 ml/kg). All patients tolerated PEG administration without adverse effects. Two dogs had additional radiographs performed, consistent with radiographic improvement of impaction. Each dog had marked clinical improvement and was successfully discharged from the hospital.